1985
DOI: 10.1302/0301-620x.67b2.3980534
|View full text |Cite
|
Sign up to set email alerts
|

Stemmed revision arthroplasty for aseptic loosening of total knee replacement

Abstract: Fifty-three failed knee replacements were revised using minimally constrained implants with smooth uncemented intramedullary stems and metal-backed tibial components. Polymethylmethacrylate was used only to replace lost bone near the surface of the implant. Excluding four knees which had serious postoperative complications, 91% had successful relief of pain, 84% had over 90 degrees of movement and 80% could walk for more than 30 minutes. Review of the radiographs showed that there were no progressive lucencies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(41 citation statements)
references
References 8 publications
5
34
0
1
Order By: Relevance
“…Previous studies have shown 32% to 61% of fully cemented stems and 10% to 74% of hybrid cementless stems have adjacent radiolucencies [4,7,13,14,17,26,32]. Although the majority of these studies used the Knee Society radiographic scoring system to evaluate radiolucencies, they categorized radiolucencies based on progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown 32% to 61% of fully cemented stems and 10% to 74% of hybrid cementless stems have adjacent radiolucencies [4,7,13,14,17,26,32]. Although the majority of these studies used the Knee Society radiographic scoring system to evaluate radiolucencies, they categorized radiolucencies based on progression.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies report 2% to 26% prevalence of radiolucent lines along cemented and uncemented tibial stems; radiolucencies were more common along the tibial rather than femoral implants [4,14,17,28,31,32]. At least one other study has also shown a higher radiographic failure rate in tibial stems as compared with femoral stems [32].…”
Section: Discussionmentioning
confidence: 99%
“…There are currently no direct comparative studies assessing the effects of revision reason on functional outcome and satisfaction, with studies combining results from aseptic revisions without substratifying those performed for aseptic loosening against other reasons. In one of the few studies to examine revisions performed for aseptic loosening, Bertin et al [4] found 91% of 53 patients who had revisions reported relief of pain and 80% could walk for more than 30 minutes. A study of revisions performed for stiffness showed low postoperative Knee Society scores and only modest improvements in scores at a mean of 43 months after surgery (postoperative Knee Society pain score, 46.9 (improvement, 31.9); postoperative Knee Society function score, 58.4 (improvement, 18.4)) [22].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] The reason is that stem extensions have improved survivorship time and clinical outcomes of revision surgery for TKRs. [1][2][3][4]11 Revision TKR surgery is a difficult procedure that requires the use of stem extensions to allow for endosteal referencing, bypassing of bone defects, and reduction of interface stresses of damaged bone in the distal femur or proximal tibia. 12 Although some investigators believe that cemented fixation of stems is the best choice to achieve optimal clinical outcome and mechanical stability for revision TKR surgery, 7,13,14 other researchers have shown that cementless stems can have mechanical superiority or equivalence relative to cemented devices.…”
Section: Introductionmentioning
confidence: 99%